2020
DOI: 10.1038/s41598-020-66905-x
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient synchronization of sheep skin fibroblasts at G2/M phase and isolation of sheep Y chromosomes by flow cytometric sorting

Abstract: that with whole genome sequencing, enrichment of Y chromosomes before sequencing might simplify data analysis and reduce sequencing costs. Flow cytometric sorting is attractive because of its capacity to purify single chromosomes in large numbers. Moreover, in recent years, sequencing technology has advanced to permit the sequencing of single chromosomes of interest isolated by flow cytometric sorting. This method has been successfully applied in humans 5,6 , gorillas 1 , Chinese hamsters 7 , and some plant sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Only approximately 5% of cells in normal culture conditions are in the division phase when observed at any given time [ 17 , 18 ]. To improve the statistical efficiency of the observations, we used a double thymidine blocking method to synchronize HeLa cells ( Figure 1c ) [ 19 ]. The number of intracellular LDs was also increased to further improve observation efficiency by treating the cells with oleic acid 24 h before fixation [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only approximately 5% of cells in normal culture conditions are in the division phase when observed at any given time [ 17 , 18 ]. To improve the statistical efficiency of the observations, we used a double thymidine blocking method to synchronize HeLa cells ( Figure 1c ) [ 19 ]. The number of intracellular LDs was also increased to further improve observation efficiency by treating the cells with oleic acid 24 h before fixation [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flow sorting of chromosomes has been utilized in the preparation of genomic libraries, chromosome paints, mapping of genetic markers and was crucial in the early stages of the “Human Genome Project” (Ibrahim & Van Den Engh, 2004; Monard, 2016; Van Dilla et al, 1986; Van Dilla & Deaven, 1990). In addition to application in human disease research, flow karyotyping and sorting has been crucial to isolate and understand the chromosomes of plants and animal (Doležel et al, 2021; Yao et al, 2020). Yao et al, 2020 have shown the effectiveness of flow karyotyping and sorting in isolating complex chromosomes of sheep prior to sequencing.…”
Section: Flow Cytometry For Chromosome Analysismentioning
confidence: 99%
“…In addition to application in human disease research, flow karyotyping and sorting has been crucial to isolate and understand the chromosomes of plants and animal (Doležel et al, 2021; Yao et al, 2020). Yao et al, 2020 have shown the effectiveness of flow karyotyping and sorting in isolating complex chromosomes of sheep prior to sequencing. This approach has then been applied to study chromatin conformation, BAC library construction, optical mapping and sequencing amplified chromosomal DNA of plants (Doležel et al, 2021).…”
Section: Flow Cytometry For Chromosome Analysismentioning
confidence: 99%
“…To date, no study has been conducted to characterize the molecular structure and function of the ovine PRAMEY [ 24 ]. This study aimed to clone the full-length cDNA of ovine PRAMEY and determine its expression patterns, as well as to investigate its CNV in different sheep breeds and the association of CNV with testicular size in Hu sheep.…”
Section: Introductionmentioning
confidence: 99%